Equivalence and recognition abroad of registered unions between two persons - Pretelli, Ilaria (CUADERNOS DE DERECHO TRANSNACIONAL, 2019)
This paper analyses the current existing models of “civil unions” in comparative perspective with a view to identify the conditions for their exportability. Their exportability is also a ground for identifying the most suitable model for a pos-sible future harmonisation of civil unions and, in this respect, to verify whether, following a Scandinavian trend, the traditional marriage, transmuted into a marriage between two neutral beings, could represent such model. Four main governmental attitudes towards homosexual couples offer at present a fertile ground for conflicts of laws, whose content is explored with special reference to Switzerland, Italy and to the European Area of Freedom, Justice and Security. Ensuring full international harmony of solutions implies renouncing to basic social policy principles on family law, when these are incompatible with the model whose import is demanded by the individuals concerned. Hence, compromise solutions are found to ensure at least a partial harmony through the recognition of some of the effects attached to the foreign status, if the latter cannot be considered equivalent to a correspondent domestic one. The limping unions that result are often far from unpredictable, and rather enshrine a political vision aimed at influencing legislative policies.
Keywords: homosexual couples; matrimonial property; civil unions; recognition of foreign acts; and equivalence